Intraoperative electrophysiological monitoring determines the final electrode position for pallidal stimulation in dystonia patients - Baláž, Marek; Búřil, Jiří; Jurková, Tereza; Koriťáková, Eva; Hrabovský, Dušan; Kunst, Jonáš; Bártová, Petra; Chrastina, Jan (Frontiers in Surgery, 2023)
Background: Bilateral deep brain stimulation (DBS) of the globus pallidus internus (GPi) is an effective treatment for refractory dystonia. Neuroradiological target and stimulation electrode trajectory planning with intraoperative microelectrode recordings (MER) and stimulation are used. With improving neuroradiological techniques, the need for MER is in dispute mainly because of the suspected risk of hemorrhage and the impact on clinical post DBS outcome. Objective: The aim of the study is to compare the preplanned GPi electrode trajectories with final trajectories selected for electrode implantation after electrophysiological monitoring and to discuss the factors potentially responsible for differences between preplanned and final trajectories. Finally, the potential association between the final trajectory selected for electrode implantation and clinical outcome will be analyzed. Methods: Forty patients underwent bilateral GPi DBS (right-sided implants first) for refractory dystonia. The relationship between preplanned and final trajectories (MicroDrive system) was correlated with patient (gender, age, dystonia type and duration) and surgery characteristics (anesthesia type, postoperative pneumocephalus) and clinical outcome measured using CGI (Clinical Global Impression parameter). The correlation between the preplanned and final trajectories together with CGI was compared between patients 1-20 and 21-40 for the learning curve effect. Results: The trajectory selected for definitive electrode implantation matched the preplanned trajectory in 72.5% and 70% on the right and left side respectively; 55% had bilateral definitive electrodes implanted along the preplanned trajectories. Statistical analysis did not confirm any of the studied factors as predictor of the difference between the preplanned and final trajectories. Also no association between CGI and final trajectory selected for electrode implantation in the right /left hemisphere has been proven. The percentages of final electrodes implanted along the preplanned trajectory (the correlation between anatomical planning and intraoperative electrophysiology results) did not differ between patients 1-20 and 21-40. Similarly, there were no statistically significant differences in CGI (clinical outcome) between patients 1-20 and 21-40. Conclusion: The final trajectory selected after electrophysiological study differed from the preplanned trajectory in a significant percentage of patients. No predictor of this difference was identified. The anatomo-electrophysiological difference was not predictive of the clinical outcome (as measured using CGI parameter).